THE REST OF SECULARISATION: ISSUES AND IMPACTS ON ISLAMIC EDUCATION - Rasyid Anwar Dalimunthe; Saripuddin Daulay; Lusinta Rehna Ginting; Mely Nadia (Proceeding International Seminar of Islamic Studies, 2022)
: The purpose of writing this article is to clearly describe the issues and impacts of the secularization of Islamic education. Because Islamic education is faith education and charity education. Islamic teachings contain teachings about personal attitudes and behavior of the community towards the welfare of individual life and living together, so Islamic education is individual education and community education. The turn of time and the times that are getting faster in the lives of Muslims are certainly many things that are a concern and even the challenges they face. Recently, we have intensified the issue of secularism, where the understanding is contrary to the concept of Islamic education that is understood and studied. The methodology used is library research. The results of a literature search on issues of secularization are that students in schools are not allowed to pray in classrooms, science and technology are not religious values, have abortions which are legal in the West, male sperm can be preserved and can be recovered. bought by the needy to get offspring. While the impact opens the door for the growth of atheism, opens the door wide for moral decay, fades faith in the unseen, shifts in values and norms and separates religious nuances from education. The implications of this discussion, in particular, serve as guidelines for Islamic religious educators to be aware of the spread of secularism in students as well as so that educators equip students with an understanding of the dangers of secularism.Keywords: Secularization, Issues and Impact, Islamic Education